2020
DOI: 10.26434/chemrxiv.11871402.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repurposing Therapeutics for COVID-19: Supercomputer-Based Docking to the SARS-CoV-2 Viral Spike Protein and Viral Spike Protein-Human ACE2 Interface

Abstract: The novel Wuhan coronavirus (SARS-CoV-2) has been sequenced, and the virus shares substantial similarity with SARS-CoV. Here, using a computational model of the spike protein (S-protein) of SARS-CoV-2 interacting with the human ACE2 receptor, we make use of the world's most powerful supercomputer, SUMMIT, to enact an ensemble docking virtual high-throughput screening campaign and identify small-molecules which bind to either the isolated Viral S-protein at its host receptor region or to the S protein-human ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Furthermore, as observed in prediction models that quercetin binds SARS-CoV-2 S-protein at its host receptor region or to the S-protein-human ACE2 interface interfering the virus entry into cells indicating its therapeutic potential (110). This prediction is consistent with the reports that both quercetin and a structurally similar luteolin inhibits the SARS-CoV virus infection (111).…”
Section: Quercetinsupporting
confidence: 89%
“…Furthermore, as observed in prediction models that quercetin binds SARS-CoV-2 S-protein at its host receptor region or to the S-protein-human ACE2 interface interfering the virus entry into cells indicating its therapeutic potential (110). This prediction is consistent with the reports that both quercetin and a structurally similar luteolin inhibits the SARS-CoV virus infection (111).…”
Section: Quercetinsupporting
confidence: 89%
“…Previous studies indicate that quercetin can suppress the replication of RNA viruses-like influenza and coronavirus. Quercetin is reported to inhibit SARS CoV2 (spike protein) attachment to ACE2 and thus interfering with the endocytosis or entry of SARS CoV2 into cells and thus act as an anti-SARS CoV2 agent (Smith and Smith, 2020). Moreover, a better anti-corona virus effect was found with quercetin, when combined with vitamin C, thus demonstrating their immunomodulatory and anti-viral properties.…”
Section: Quercetinmentioning
confidence: 98%
“…Similarly, oxidative stress and inflammation result in altered immune response (innate and acquired immunity) which plays a dominant role in the pathophysiology of COVID-19 (Leisman et al, 2020). Furthermore, studies have indicated that elevated ROS production (oxidative burs/stress), cytokine storm (inflammation), immune dysfunction end up in multi-organ failure by altering various normal cellular functions like autophagy, apoptosis, necrosis (cell death), cell energy system (mitochondrial dysfunction) along with altered microbiota flora (microbiota dysbiosis) could increase the severity of SARS-CoV2 infection (Yuki et al, 2020;Smith et al, 2020).…”
Section: An Overview On the Pathophysiology Of Covid-19mentioning
confidence: 99%
“…According to a computational docking model, some small molecules can be identified. These molecules are competent to restrict viral recognition of host cells and/or interfere with host-virus interactions by virtue of binding to the isolated viral S protein or the S protein-human ACE2 receptor interface [19].…”
Section: Potential Of Quercetin In Curing the Sars-cov-2mentioning
confidence: 99%